2008
DOI: 10.1016/j.ijid.2008.05.364
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Safety Evaluation of An AS-Adjuvanted H5N1 Prepandemic Candidate Vaccine in Children Aged 3–9 Years: A Phase II Study

Abstract: Two telephone surveys were conducted during October 3-11 and December 15-17, 2007 targeting people aged 65 and older randomly sampled by the Computer Assisted Telephone Interview (CATI). Questionnaires were developed under the theoretical framework of the health belief model. Among 1,115 effective samples of pre-survey, 512 (45.9%) were successfully followed.512 people of post-survey were representative of pre-survey population because of their comparability of demographic characteristics. 62.6% (698/1,115) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Vaccines containing ASO3 have been evaluated in thousands of individuals. ASO3-H5N1 vaccine has been reported to be safe in both adults and children [36,37]. The vaccine has been reported to be immunogenic, to be dose sparing, and to induce cross-clade immune responses [38,39].…”
Section: The Development Of Oil-in-water Emulsions As Adjuvants For Fmentioning
confidence: 99%
“…Vaccines containing ASO3 have been evaluated in thousands of individuals. ASO3-H5N1 vaccine has been reported to be safe in both adults and children [36,37]. The vaccine has been reported to be immunogenic, to be dose sparing, and to induce cross-clade immune responses [38,39].…”
Section: The Development Of Oil-in-water Emulsions As Adjuvants For Fmentioning
confidence: 99%
“…The candidate H5N1 AS03-adjuvanted vaccine did not raise any safety concerns and the reactogenicity profile was considered to be clinically acceptable 52,53…”
Section: Gsk Influenza Vaccine Portfoliomentioning
confidence: 99%
“…49 In children aged 3-9 years, the vaccine containing 1AE9 lg HA (A⁄ Vietnam ⁄ 1194 ⁄ 2004) adjuvanted with AS03 demonstrated marked cross-clade immunogenicity. 50 Safety and reactogenicity profiles of PrepandrixÔ In the study by Leroux-Roels et al, 39 the most common adverse event was injection site pain, reported by 90% of subjects receiving the adjuvanted 3AE75 lg HA formulation within 7 days after vaccination. Pain was reported significantly less frequently (38%) in the non-adjuvanted 3AE75 lg group (P < 0AE0001).…”
Section: Immunogenicity Of Prepandrixômentioning
confidence: 99%
See 2 more Smart Citations